Integrated Single Superphosphate with Cattle Manure Increased Growth, Yield, and Phosphorus Availability of Maize (Zea mays L.) Under Rainfed Conditions - Samraiz Ali; Abid Ali (Nitrogen)
Mostly, phosphorus (P) fertilizers are fixed in the interlayer of soil and become unavailable to crop plants. Combined inorganic fertilizers with organic manures could be a suitable solution to release these nutrients from the soil. P deficiency in soil adversely affected crop growth and development to a larger extent. To check out this problem, present research was conducted over a two-year period to evaluate the efficiency of a combined mixture of inorganic P and organic manure as a better farming strategy, in relation to their sole treatments, for enhancing P availability, plant growth, yield and quality, and soil properties. The inorganic source of P was SSP in the form of P2O5, while the organic source was cattle manure mixed with crop residues called farmyard manure (FYM). The experiment consisted of the same six treatments over each year: (i) control (0F+0P), (ii) 45 kg P2O5 ha−1 (45P), (iii) 90 kg P2O5 ha−1 (90P), (iv) 45 kg P2O5 ha−1 + 1000 kg FYM ha−1 (45P+1000F), (v) 1000 kg FYM ha−1 (1000F), and (vi) 2000 kg FYM ha−1 (2000F), using randomized complete block design (RCBD), to five replications. Results demonstrated that the combination of SSP with FYM increased the plant height (27.9%), grain yield (23.4%), and plant P uptake efficiency (43.7%) of maize as compared to sole SSP at 90 kg P2O5 ha−1, which occurred due to improved P availability in soil. By comparing sole amendments of P fertilizer sources, FYM-treated plots have performed better in increasing maize growth and yield components such as plant height, dry matter, crop growth rate (CGR), net photosynthetic rate, grain yield, and crude protein (e.g., nitrogen contents); this happened due to enhanced soil chemical properties that might be related to improvement in P level and decreased bulk density of soil. Further, significant positive correlations were exhibited among studied crop and soil data. The plant available P and grain protein contents (N concentration) also showed a significant positive correlation and exhibited higher nitrogen contents under organic amendments of P fertilizer, as compared to inorganic treatments. The study concluded that combined SSP at 45 kg P2O5 ha−1 with organic cattle manure at 1000 kg ha−1 has a great potential for enhancing maize productivity under water deficit conditions. Results of this research may further be improved by including rigorous soil samples and field heterogeneity data between the plots and the years, which will provide more clear findings from a combined mixture of organic and inorganic fertilization.